Mechanical behaviour of natural coconut/banana fiber reinforced composites. Issue 1 (April 2021) - Raghul, K S; Abhiram, R; Anand, S; Ragul, R Vijay
Abstract: In today's trend, research on composites is growing, and there is always a need for alternative materials. Natural fibre reinforced composites were chosen over man-made fibres because they are easier to fabricate and use less energy. It's also affordable and has a power that's equivalent to synthetic fibres. A composite is made up of a matrix phase and a non-matrix phase. A composite is made up of two phases: matrix and reinforcement. Resin + hardener are the matrix phases used. It is a primary phase that has a constant shape. This step is normally more ductile and less hard. coconut and banana fibre form the reinforcing process, which has a discontinuous form. As compared to matrix process, it normally has more power. The properties of a 0%, 1%, 3% and 5% of nano material imposition were compared. In comparison a plate with 5% Nano Silica has maximum (tensile & flexural) strength. The plate with a 1% Nano silica has the highest impact strength.